PERAN PEMERINTAH DALAM PENGELOLAAN TERMINAL DI TERMINAL REGIONAL DAYA KOTA MAKASSAR - Muhammad Aslan; Muhlis Madani; Nuraeni Aksa (Department of Public Administration, Muhammadiyah University of Makassar, 2015)
This research aims to know government role and governmental step in management of Terminal Regional Daya Makassar City. It executed in Company of Area ‘PD. Terminal Makassar Metro’. Type of this research is descriptive qualitative with source of primary and secondary data. Data are obtained by observation, interview and documentation. Data are analyzed by reduction, display data and verification later conducted anticipatory. Result of research indicates that governmental role in management of terminal is not yet optimal, which is supported by result of field observation and interview. As facilitator, motivator and regulator, government is not maximal in applying of relevant regulation of terminal, less co-ordinate and observation. Governmental steps in managementof terminal are planning, budgeting, and implementing management of terminal. Keywords: role of government, management, terminal Penelitian ini bertujuan mengetahui peran pemerintah dan langkah pemerintah dalam pengelolaan Terminal Regional Daya Kota Makassar. Dilaksanakan di Perusahaan Daerah “PD. Terminal Makassar Metro”. Jenis penelitian deskriptif kualitatif dengan sumber data primer dan data sekunder. Data diperoleh melalui observasi, dokumentasi dan wawancara. Data dianalisis secara reduction, display data dan verificationkemudian dilakukan anticipatory. Hasil penelitian menunjukkan bahwa peran pemerintah dalam pengelolaan terminal belum optimal, yang mana didukung oleh hasil observasi lapangan dan wawancara. Sebagai fasilitator, motivator dan regulator, pemerintah tidak maksimal dalam penerapan peraturan terkait terminal, kurang melakukan koordinasi dan pengawasan. Langkah pemerintah dalam pengelolaan terminal ialah perencanaan, penganggaran, dan implementasi pengelolaan terminal. Kata kunci: peran pemerintah, pengelolaan, terminal